2005
DOI: 10.1007/s11111-005-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics and Tropical Deforestation: State of the Debate and Conceptual Challenges

Abstract: What is the role of population in driving deforestation? This question was put forth as a discussion topic in the cyberseminar hosted by Population Environment Research Network (PERN) in Spring, 2003. Contributors from diverse backgrounds weighed in on the discussion, citing key factors in the population-deforestation nexus and suggesting further courses of action and research. Participants explored themes of their own choosing, with many coming to the forefront. Scale, time, and placebased effects were cited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 77 publications
3
78
0
10
Order By: Relevance
“…Previous research has suggested that increasing urbanization can flatten the EKC (Carr et al 2005); migration by farmers and workers to the cities can reduce the pressure on the forests from subsistence farming (Perz & Skole 2003, Rudel et al 2005. Additionally, urban areas tend to experience more substitution of wood products, both in terms of energy and building materials (Ehrhardt-Martinez et al 2002).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has suggested that increasing urbanization can flatten the EKC (Carr et al 2005); migration by farmers and workers to the cities can reduce the pressure on the forests from subsistence farming (Perz & Skole 2003, Rudel et al 2005. Additionally, urban areas tend to experience more substitution of wood products, both in terms of energy and building materials (Ehrhardt-Martinez et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The constant clearing of forest land partly occurs to create more livestock ranches, which generally produce more money than do crops (Carr et al 2005, Perz & Skole 2003. Ranching, though, can foster a negative cycle of deforestation; forest land is cleared for livestock that then overgrazes the land and causes it to degrade, thus forcing further expansion of the ranches into more forest area (Allen & Barnes 1985).…”
Section: Selected Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between population growth and environmental changes is still an area of active debate (Alexandratos 2005;Carr et al 2005;Grau et al 2008;Jha and Bawa 2006;Nyssen et al 2004). In Ethiopia, population growth increases the demand for arable land and encourages the conversion of forests to agriculture.…”
Section: Model Validationmentioning
confidence: 99%
“…These processes have the potential to increase deforestation-for a recent discussion of the literature on population dynamics and deforestation, see Carr, Suter, and Barbieri (2005). Rudel and Roper (1997) describe how deforestation comes about in their "immiserization" and "frontier" models of development.…”
Section: Neo-malthusian Theorymentioning
confidence: 99%